Zeolite-based organic-inorganic hybrid catalysts for phosgene-free and solvent-free synthesis of cyclic carbonates and carbamates at mild conditions utilizing CO2 - Srivastava, R; Srinivas, D; Ratnasamy, P (Applied Catalysis A - General, 2005)
As-synthesized zeolite-beta exhibits high catalytic activity for the synthesis of cyclic carbonates and alkyl and aryl carbarnates by a phosgene-free route, utilizing the greenhouse effect gas CO2. The reaction occurs with high yields of the desired products at mild conditions and without using any solvent or cocatalyst. Cyclic carbonates are synthesized by cycloaddition reaction Of CO2 with oxiranes (epichlorohydrin, propene oxide, styrene oxide and n-butene oxide) at 393 K and 6.9 bar. Alkyl and aryl carbarnates are synthesized by the reaction of the corresponding amines, CO2 and n-butyl bromide at 353 K and 3.4 bar. The as-synthesized zeolite-beta containing the encapsulated quaternary ammonium ions is not only reusable in several recycling experiments, but also shows superior activity to that of the corresponding homogeneous, quaternary ammonium halide salt generally used in the commercial synthetic practice. The microporous silica (inorganic) acting in concert with the encapsulated organic component constitutes an efficient, recyclable catalyst for this reaction. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: alkyl and aryl carbamates; carbon dioxide utilization; cyclic carbonate; phosgene-free synthetic route; Polycarbonate; zeolite-beta

Fe-Zn double-metal cyanide complexes as novel, solid transesteritication catalysts - Srivastava, R.; Srinivas, D.; Ratnasamy, P. (Journal of Catalysis, 2006)
Fe-Zn double-metal cyanide complexes are currently used as catalysts for the ring-opening polymerization of epoxides, as well as the coupling of epoxides and CO2 for the production of polycarbonates. We report their novel application as highly efficient solid catalysts for the transesterification reactions of carbonates. The catalysts were prepared from aqueous solutions of ZnCl2 and K4Fe(CN)(6) in the presence of tert-butanol (complexing agent) and tri-block copolymer EO20PO70EO20 (average molecular weight, 5800; co-complexing agent). They were characterized by chemical analysis, XRD, thermal analysis, N-2 adsorption, magnetic susceptibility, SEM, and FTIR, diffuse reflectance UV-visible, EPR, and X-ray photoelectron spectroscopies. Their acidity was determined from the IR spectra of adsorbed pyridine and the temperature-programmed desorption of NH3. Catalyst samples prepared with both complexing and co-complexing agents were found to be more acidic and catalytically active than those prepared without these agents. These catalysts are more active/selective than other solid catalysts hitherto reported. Dimethyl carbonate, for example, could be synthesized with 100% selectivity and an isolated yield of >86% by the reaction of propene carbonate with methanol. The catalysts can be recycled without significant loss in activity. Lewis acidic Zn ions are the possible active sites for the transesterification reaction. (c) 2006 Published by Elsevier Inc.
Keywords: cyclic carbonate; Dimethyl carbonate; double metal cyanide Fe-Zn complexes; organic carbonate; transesterification catalyst

Highly selective synthesis of mono-ethylene glycol phenyl ethers via hydroxyalkoxylation of phenols by cyclic carbonates using large pore zeolites - Kinage, Anil K.; Gupte, Sunil P.; Chaturvedi, Rajiv K.; Chaudhari, Raghunath V. (Catalysis Communications, 2008)
Hydroxyalkoxylation of phenols by cyclic carbonates catalyzed by alkali loaded large pore zeolites has been reported. The study shows that KL type zeolite was recyclable and selective in producing mono-ethylene glycol pheryl ethers in similar to 98.5% yield. Various substituted simple phenols were converted into mono-ethylene glycol ether of phenols with over 90% yields, except 3-bromo and 2-methyl phenols. Mono hydroxyl plienols such as hydroquinone, biphenol and BPA (2,2-bis(4-hydroxyphenyl)propane) also produce corresponding mono- and di-ethylene glycol ethers. The ratio of ethylene carbonate to phenol was found to be critical for selective formation of monoethylene glycol phenyl ether of phenols. A ratio of two results in formation of appreciable amount of diether derivative viz., 2-(2-phenoxyethoxy) ethanol. Compared to ethylene carbonate, a lower reactivity of 1,2-propane carbonate was found for hydroxyalkoxylation of phenol. It was found that ring opening at less hindered methylene carbon of 1,2-propylene carbonate prevailed giving rise to selective formation of beta-hydroxy phenyl ethers. The reactivity of ethylene carbonate towards O-alkylation versus transesterification of phenol has been explained on the basis of HSAB concept. Finally, it has been shown that yield of mono-ethylene glycol phenyl ether is controlled both by basicity and channel architecture of zeolite structure. KL zeolite was found to be the most effective zeolite because of it's intermediate basicity and one dimensional channel architect. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: cyclic carbonate; ethylene glycol phenyl ether; hydroxyalkoxylation; phenol

New ATRP initiator for synthesis of cyclic carbonate-terminated poly(methyl methacrylate) - Palaskar, Dnyaneshwar V.; Sane, Prakash S.; Wadgaonkar, Prakash P. (Reactive & Functional Polymers, 2010)
A new ATRP initiator, viz, 2-oxo-1,3-dioxolan-4-yl-(methyl-2-bromo-2-methylpropanoate) (ODMBMP) was synthesized by the reaction of commercially available glycerol carbonate with 2-bromoisobutyrylbromide and was used to carry out ATRP reactions of methyl methacrylate (MMA) in the presence of copper chloride/N,N',N',N''N''-pentamethyldiethylenetriamine to afford low molecular weight (M(n)(GPC) = 1750-7550) cyclic carbonate-terminated poly(methyl methacrylate)s with relatively narrow molecular weight distribution (M(w)/M(n) = 1.16-1.30). Poly(methyl methacrylate)s having higher molecular weight (M(n)(GPC) = 18,250 and 44,130) could also be synthesized using ODMBMP as the ATRP initiator. The kinetic studies of bulk ATRP of MMA showed a linear relationships between both In[M](o)/[M(t)] vs time and molecular weight vs conversion indicating controlled/living polymerization. The presence of cyclic carbonate functionality in poly(methyl methacrylate)s was confirmed by FUR. (1)H NMR, and (13)C NMR spectroscopy. The reactivity of cyclic carbonate group was demonstrated by a model reaction using n-propyl amine and the results showed quantitative conversion to hydroxyl urethane group. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Atom transfer radical polymerization (ATRP); cyclic carbonate; functional polymers; poly(methyl methacrylate)

Versatile Cu-II metal-organic framework exhibiting high gas storage capacity with selectivity for CO2: conversion of CO2 to cyclic carbonate and other catalytic abilities - De, Dinesh; Pal, Tapan K.; Neogi, Subhadip; Senthilkumar, S.; Das, Debasree; Sen Gupta, Sayam; Bharadwaj, Parimal K. (Chemistry-A European Journal, 2016)
A linear tetracarboxylic acid ligand, H4L, with a pendent amine moiety solvothermally forms two isostructural metal-organic frameworks (MOFs) L-M (M=Zn-II, Cu-II). Framework L-Cu can also be obtained from L-Zn by post- synthetic metathesis without losing crystallinity. Compared with L-Zn, the L-Cu framework exhibits high thermal stability and allows removal of guest solvent and metal-bound water molecules to afford the highly porous, L-Cu. At 77K, L-Cu absorbs 2.57wt% of H-2 at 1bar, which increases significantly to 4.67wt% at 36bar. The framework absorbs substantially high amounts of methane (238.38cm(3)g(-1), 17.03wt%) at 303K and 60bar. The CH4 absorption at 303K gives a total volumetric capacity of 166cm(3)(STP)cm(-3) at 35bar (223.25cm(3)g(-1), 15.95wt%). Interestingly, the NH2 groups in the linker, which decorate the channel surface, allow a remarkable 39.0wt% of CO2 to be absorbed at 1bar and 273K, which comes within the dominion of the most famous MOFs for CO2 absorption. Also, L-Cu shows pronounced selectivity for CO2 absorption over CH4, N-2, and H-2 at 273K. The absorbed CO2 can be converted to value-added cyclic carbonates under relatively mild reaction conditions (20bar, 120 degrees C). Finally, L-Cu is found to be an excellent heterogeneous catalyst in regioselective 1,3-dipolar cycloaddition reactions (click reactions) and provides an efficient, economic route for the one-pot synthesis of structurally divergent propargylamines through three-component coupling of alkynes, amines, and aldehydes.
Keywords: click reactions; CO2 absorption; cyclic carbonate; heterogeneous catalysis; metal-organic frameworks

Activity performance and kinetics for glycerol carbonylation with urea over Zn-Co mixed metal oxide catalyst - Kondawar, Sharda E.; Kasar, Gaytri B.; Khatua, Angshuman S.; Rode, V, Chandrashekhar (Canadian Journal of Chemical Engineering, 2023)
Efficient carbonylation of glycerol using urea with Zn-Co mixed metal oxide (MMO) catalyst has been achieved. Various methods of catalyst preparation were explored for glycerol carbonate (GC) synthesis. The optimized method of catalyst preparation was found to be co-precipitation (CP) with a Zn:Co ratio of 70:30, achieving 81% glycerol conversion with 97% GC selectivity. X-ray diffraction (XRD) studies revealed the formation of ZnO, Co-3 O-4, and spinel ZnCo2O4 phases. Thermal treatment given to the catalyst allows insertion of Zn cations into Co3O4 lattice forming ZnCo2O4 phase which was also evidenced in X-ray photoelectron spectroscopy (XPS) and Raman spectroscopy. Herein, for the first time, reaction kinetics was studied to propose the rate equation, based on which a plausible reaction pathway is proposed involving two-site adsorption of glycerol (basic site) and urea (acidic site), which undergo carbonylation followed by cyclization into GC. A recycle study and hot filtration test have proven the reusability of the catalyst.
Keywords: Carbonylation; cyclic carbonate; Glycerol; kinetics; mixed metal oxide